Extended-spectrum β-lactamases, transferable quinolone resistance, and virulotyping in extra-intestinal E. coli in Uruguay - Rafael Vignoli; Virginia García-Fulgueiras; Nicolás F Cordeiro; Inés Bado; Verónica Seija; Paula Aguerrebere; Gabriel Laguna; Lucía Araújo; Cristina Bazet; Gabriel Gutkind; José Chabalgoity (Journal of Infection in Developing Countries)
Introduction: To characterize extended-spectrum β-lactamases (ESBLs) and plasmid-mediated quinolone resistance (PMQR) genes in Escherichia coli isolates obtained from extra-intestinal samples in three Uruguayan hospitals. Methodology: Fifty-five ESBL-producing E. coli isolates were studied. Virulence genes, ESBLs, and PMQR genes were detected by polymerase chain reaction.  ESBL-producing isolates were compared by pulsed-field gel electrophoresis. Multi-locus sequence typing was also performed on 13 selected isolates. Results: Thirty-seven isolates harbored blaCTX-M-15 (67.3%), eight blaCTX-M-2 (14.6%), five blaCTX-M-14 (9.1%), three carried both blaCTX-M-2 and blaCTX-M-14, one blaCTX-M-9, and one blaCTX-M-8.  Among the CTX-M-15 producers, 92% belonged to sequence types ST131 and ST405, and carried aac(6’)Ib-cr as well. Isolates harboring blaCTX-M-2, blaCTX-M-14, blaCTX-M-9, or blaCTX-M-8 were found to be genetically unrelated. Conclusions: The successful dissemination of CTX-M-15-producing E.coli isolates seems to be linked to the spreading of high-risk clones and horizontal gene transfer. A trade-off between carrying more antibiotic resistance and less virulence-related genes could partially account for the evolutionary advantages featured by successful clones.